2018
DOI: 10.18393/ejss.337218
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of land suitability for main irrigated crops in the North-Western Region of Libya

Abstract: Land suitability analysis can help to achieve sustainable crop production with a proper use of the natural resources. The current study was carried out on the soils of northwestern area of Libya to assess their morphological, physical and chemical properties and their suitability for growing irrigated crops. The studied area lies between latitudes 32° 30′ 00.9" and 32° 57′ 34.2'' N and between longitudes 11° 35′ 08.4" and 11° 45′ 09.2" E. Two suitability methods (Sys &Verhey and Storie methods) were used to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Using Sentinel 2 images leads to increased clarification details of landscape where the high and low lands, basin and wadis boundaries were identified [30,62,63]. The soils that are located in southern parts of the study area were classified as Lithic Torripsamments, whereas the soil profiles' depth is very shallow and this is considered as a main obstacle to soil capability and crop suitability [64,65]. On the contrary, the soil types Typic Torripsaments, Typic Torrifluvents and Typic Haplocalcids were allocated in the wadi, decantation basins and sand plain geomorphic units with deep soil The geomorphic units such as the plateau, escarpment and ridge were not considered in the suitability evaluation, which represents 28% of the total study area.…”
Section: Geomorphology and Soilsmentioning
confidence: 99%
“…Using Sentinel 2 images leads to increased clarification details of landscape where the high and low lands, basin and wadis boundaries were identified [30,62,63]. The soils that are located in southern parts of the study area were classified as Lithic Torripsamments, whereas the soil profiles' depth is very shallow and this is considered as a main obstacle to soil capability and crop suitability [64,65]. On the contrary, the soil types Typic Torripsaments, Typic Torrifluvents and Typic Haplocalcids were allocated in the wadi, decantation basins and sand plain geomorphic units with deep soil The geomorphic units such as the plateau, escarpment and ridge were not considered in the suitability evaluation, which represents 28% of the total study area.…”
Section: Geomorphology and Soilsmentioning
confidence: 99%
“…Additionally, they applied a qualitative model for evaluating soil suitability to assist decision makers for sustainable agriculture planning and economic productivity of soil resources in Iran. While, in the north-western region of Libya, Reference [86] reported that the main limiting factors of soil suitability for wheat, maize, alfalfa, sunflower, soybean, potato, citrus, and olives crops were soil salinity, soil texture, alkaline pH, calcium carbonate, and soil depth. Their findings are consistent with this research's observations.…”
Section: Soil Suitability Subclassesmentioning
confidence: 99%
“…The fitness of land for a defined use is termed as land suitability (Shyju1 and Kumaraswamy, 2019). Land suitability assessment is defined as the process of land performance assessment to predict the potential land for crop production (FAO, 1976;FAO, 1978;Pan and Pan, 2012;Darwish and Abdel Kawy, 2014;Ahmed, 2016;AbdelRahman et al, 2016 andAbd El-Aziz, 2018), and identifying the main limiting factors for the agricultural production and enables decision makers to increase the land productivity (AbdelRahman et al, 2016). Assessment of land suitability potentials is an important step to detect the environmental limit for sustainable land management (SLM) (Zolekar and Bhagat, 2018).…”
Section: Introductionmentioning
confidence: 99%